Factors Related to the Work Performance of Midwives in the IUD Contraception Service in Primary Healthcare Centers of Surabaya City - Yasi Anggasari; Martha Irene Kartasurya; Anneke Suparwati (Jurnal Manajemen Kesehatan Indonesia, 2013)
Penurunanangka cakupan peserta KB aktif IUD di Surabaya dalam 3 tahun terakhir dari 12,27%menjadi 6,1% menjadi perhatian khusus Dinas Kesehatan Kota Surabaya, hal ini terjadi akibatbelum optimalnya kinerja bidan dalam pelayanan kontrasepsi IUD di Puskesmas wilayahSurabaya. Tujuan penelitian menganalisis faktor-faktor yang berhubungan dengan kinerja bidandalam pelayanan kontrasepsi IUD di Puskesmas Wilayah Kota Surabaya.Penelitian analitikobservasional ini dilakukan dengan pendekatan cross sectional. Populasi penelitian adalahseluruh bidan di Puskesmas kota Surabaya yang memberikan pelayanan KB dan telah mengikutipelatihan CTU (362 bidan). Subjek penelitian 78 responden dipilih secara proporsional stratifiedrandom sampling. Pengumpulan data dilakukan dengan wawancara terstruktur dan observasi.Analisis data menggunakan uji regresi linear ganda.Hasil penelitian menunjukkan kinerja bidandalam pelayanan kontrasepsi IUD di wilayah Kota Surabaya 55,1 % dalam kategori baik.Pengetahuan bidandalam pelayanan kontrasepsi IUD (82,1%) kurang baik khususnya dalam halpenapisan dan konseling pra pemasangan. Motivasi bidan (55,1%) baik, sikap bidan (51,3%)kurang mendukung dalam pelayanan kontrasepsi IUD.Persepsi bidan terhadap kepemimpinankepala puskesmas (52,6%) baik. Persepsi bidan terhadap imbalan yang didapatkan 53,8% baik.Sarana prasarana (53,8%) sudah tersedia dalam menunjang pelayanan kontrasepsi IUD.Motivasi, sikap dan persepsi kepemimpinan berhubungan dengan kinerja bidan sedangkanpengetahuan, persepsi terhadap imbalan dan sarana prasarana tidak berhubungan dengan kinerjabidan dalam pelayanan kontrasepsi IUD. Secara bersama-sama motivasi dan persepsikepemimpinan berhubungan dengan kinerja bidan dalam pelayanan kontrasepsi IUD.DisarankanDKKuntuk melaksanakan supervisi secara langsung dan berkala untuk mengevaluasi danmonitoring pelaksanaan program di setiap Puskesmas serta memberikan motivasi dalamkemudahaan izin belajar bagi bidan yang ingin melanjutkan pendidikan.  The decrease of IUD active family planning participants’ coverage in Surabaya in the last three years, from 12.27% to 6.1%, became a special attention for Surabaya district health office. The decrease was caused by inadequate work performance of midwives in implementing IUD contraception service in the primary healthcare centers in Surabaya area. Objective of the study was to analyze factors related to the work performance of midwives in the IUD contraception service in the primary healthcare centers of Surabaya city area. This was an analytical- observational study using cross sectional approach. Study population was all midwives in the primary healthcare centers in Surabaya city who provide family planning service, and who had attended in CTU training (362 midwives). Study subjects were 78 respondents, and they were selected using proportional stratified random sampling method. Data collection was conducted through structured interview and observation. Multiple linear regression tests were applied in the data analysis. Results of the study showed that work performance of midwives in the IUD contraception service in Surabaya city area was in a good category (55.1%). Midwives’ knowledge on IUD contraception service specifically on screening and counseling before insertion was insufficient (82.1%). Motivation of midwives was good (55.1%). Midwives attitude regarding IUD contraception service was not supportive (51.3%). Perception of midwives towards head of primary healthcare center leadership was good (52.6%). Midwives perception on remuneration they received was good (53.8%). Facilities to support IUD contraception service were available (53.8%).Motivation, attitude, and perception on the leadership were associated with midwives’ work performance. However, knowledge, perception of remuneration, and facilities were not associated with midwives’ work performance in the IUD contraception service. Motivation and perception on the leadership, in common, were associated with midwives’ work performance in the IUD contraception service.Suggestions for district health office was to perform supervision directly and periodically, to evaluate and monitor the implementation of program in every primary healthcare center, and to provide permission for midwives who want to take further study.